Long noncoding RNA HOTAIR regulates the invasion and metastasis of prostate cancer by targeting hepaCAM - Li, Ting (Br J Cancer, 2020)
BACKGROUND: The role of HOX transcript antisense RNA (HOTAIR) has been proven to be important in tumorigenesis. However, how this molecule promotes metastasis and invasion in PCa is still unclear. METHODS: The relationship between HOTAIR and hepatocellular adhesion molecule (hepaCAM) in PCa was identified by immunohistochemistry, immunofluorescence, plasmid transfection, quantitative real-time PCR and immunoblotting. The regulatory effects of HOTAIR on hepaCAM and MAPK signalling and their key roles in PCa metastasis were investigated in vitro. RESULTS: The expression of HOTAIR was inversely correlated with hepaCAM in the blood and tissue of PCa patients. Here, hepaCAM was identified as a novel target gene of HOTAIR and was critical for the invasiveness of PCa. HOTAIR recruited PRC2 to the hepaCAM promoter, resulting in high levels of H3K27me3 and the absence of hepaCAM with an abnormally activated MAPK pathway. Both HOTAIR depletion and EZH2 inhibition could induce hepaCAM re-expression with inhibitory MAPK signalling and decrease the invasive and metastatic capabilities of PCa cells. CONCLUSIONS: This study demonstrates that HOTAIR promotes invasion and metastasis of PCa by decreasing the inhibitory effect of hepaCAM on MAPK signalling. Therefore, the HOTAIR/hepaCAM/MAPK axis may provide a new avenue towards therapeutic strategies and prognostic indicators for advanced prostate cancer.